Case Report on Amlodipine Induced Pitting Type Pedal Edema - Sunil, Sahithya (Journal of Pharmacy Practice and Community Medicine)
Amlodipine is 1,4 dihydropyridine class of third generation calcium channel blocker which is indicated for the management of hypertension, coronary atherosclerosis, stable angina and it is also an alternative used for the nifedipine induced pedal edema. This case study aims to make report of the common adverse reaction pitting type pedal edema is occurring during the treatment with the same. Amlodipine has increased incidence rate of pedal edema compared to other calcium channel blockers. Here present 67 years old male patient who gradually develops pitting type pedal edema after the initiation of oral amlodipine for hypertension. The symptoms have been relieved after the cessation of drug and patient has been managed with alternative antihypertensive agent. This study helps to consider more regarding amlodipine therapy and aids to earlier prevention of serious adverse drug reactions occurring in patients.
Keywords: Amlodipine; Pedal edema; Calcium channel blocker; Adverse drug reaction